PREVALENCE OF ESBL-POSITIVE E. COLI ISOLATED FROM BLOOD AND PUS SAMPLES (JANUARY 2019 TO MARCH 2021) SPECIMENS AT MAKERERE UNIVERSITY CLINICAL MICROBIOLOGY LABORATORY. A CROSS-SECTIONAL STUDY. - Juan , Moureen; Nyanganda , Emma Kevin; Ayeebale, Rabeeha Nyakake; Modi, Derick; Acen , Juliet (SJ Insights, 2024)
Background Production of extended-spectrum beta-lactamase enzymes is one of the common mechanisms of resistance of Escherichia coli to antibiotics, thus timely detection and reporting of this phenotype are very critical and crucial especially when it comes to bloodstream and wound infections caused by this phenotype of E.coli. Therefore, this study sought to determine the prevalence of ESBL-Positive E.Coli isolated from blood and pus samples. Methodology This study was a cross-sectional retrospective analysis of lab records for ESBL-positive E. coli isolated from blood and pus samples received between the periods of January 2019 to March 2021 at the Makerere University Clinical Microbiology Laboratory, purposive sampling technique was used to select only records for which ESBL positive E.coli. Results For Bloodstream infections: Out of the 91 samples positive for E.coli received by the lab between the periods of January 2019 to March 2021, 50.55% (46) were ESBL positive while 46.15% (42) were ESBL negative. 3.30% (3) of the samples were not screened for ESBL production. In the majority (46) 51% of blood cultures were positive for ESBL. E.coli and 42(46%) were ESBL negative E.coli. For wound infections: Out of 85 samples positive for E.coli received by the lab between the periods of January 2019 and March 2021, 44.71% (38) were ESBL positive while 55.29% (47) were ESBL negative. The majority 47 (55.29%) of pus swabs from wound infections were ESBL negative E.coli while 38(44.71%) were ESBL positive E.coli. Conclusion 50.55% of the isolated E.coli from bloodstream infections were ESBL positive as compared to wound infections, the prevalence was 44.71%. This could pose a great risk to the management of E.coli infections. Recommendation The laboratory should play the role of guiding physicians and medical personnel on the need for infection control measures to prevent the spread of ESBL E.coli organisms.